STUDI KETERSEDIAAN PAKAN TERHADAP PERILAKU BERUK (Macaca nemestrina Linnaeus 1766) DI ARBORETUM UNIVERSITAS RIAU - Ilyas, Engki; Yoza, Defri; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Macaca nemestrina is one of the short tailed primates that vulnerable in the IUCN list and inserted in appendix II of CITES. Macaca nemestrina in habitat have a major role in protecting and preserving the balance of ecosystem. The results showed that the number of the Macaca nemestrina population in the Arboretum UR is 40 individual. Each has a number based on social status in an adult male 4 individual, 6 individual adult female, male adolenscents 8 individual, female adolenscents 12 individual and children 10 individual. The time allocation of daily activity for each individual Macaca nemestrina is rested activity 1.144,21 (31,78%) minutes, migrated activity 1.047,82 (29,11%) minutes, eat activity 851,61 (23,66%) minutes, grooming 419,03(1,64%) minutes and social interaction 137,33(3,81%). Observations availibility of Macaca nemestrina feed types based on the analysis of vegetation found 18 species of poles and 20 species of trees. The results of the analysis of vegetation poles and trees explained that are many available types of macaca nemestrina food resources. The results of the analysis of vegetation at the level of the pole and the tree indicates there are 8 types that dominated at the growth level. fromÂ 8 species that dominated there are 7 types of poles and 6 types of trees level that become the food source Â Macaca nemestrina.Â Keyword : Macaca nemestrina, population, activity, feed